Nanoarchitectonics of Bactericidal Coatings Based on CaCO3−Nanosilver Hybrids - Ferreira, Ana M.; Vikulina, Anna S.; Bowker, Laura; Hunt, John A.; Loughlin, Michael; Puddu, Valeria; Volodkin, Dmitry (ACS Applied Bio Materials, 2024)
Antimicrobial coatings provide protection against microbes colonization on surfaces. This can prevent the stabilization and proliferation of microorganisms. The ever-increasing levels of microbial resistance to antimicrobials are urging the development of alternative types of compounds that are potent across broad spectra of microorganisms and target different pathways. This will help to slow down the development of resistance and ideally halt it. The development of composite antimicrobial coatings (CACs) that can host and protect various antimicrobial agents and release them on demand is an approach to address this urgent need. In this work, new CACs based on microsized hybrids of calcium carbonate (CaCO3) and silver nanoparticles (AgNPs) were designed using a drop-casting technique. Polyvinylpyrrolidone and mucin were used as additives. The CaCO3/AgNPs hybrids contributed to endowing colloidal stability to the AgNPs and controlling their release, thereby ensuring the antibacterial activity of the coatings. Moreover, the additives PVP and mucin served as a matrix to (i) control the distribution of the hybrids, (ii) ensure mechanical integrity, and (iii) prevent the undesired release of AgNPs. Scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) techniques were used to characterize the 15 μm thick CAC. The antibacterial activity was determined against Escherichia coli, methicillin-resistant Staphylococcus aureus (MRSA), and Pseudomonas aeruginosa, three bacteria responsible for many healthcare infections. Antibacterial performance of the hybrids was demonstrated at concentrations between 15 and 30 μg/cm2. Unloaded CaCO3 also presented bactericidal properties against MRSA. In vitro cytotoxicity tests demonstrated that the hybrids at bactericidal concentrations did not affect human dermal fibroblasts and human mesenchymal stem cell viability. In conclusion, this work presents a simple approach for the design and testing of advanced multicomponent and functional antimicrobial coatings that can protect active agents and release them on demand.
CRIS-Team Scopus Importer:2024-05-31
Keywords: antimicrobial; calcium carbonate; mucin; polyvinylpyrrolidone; vaterite